Bronchial epithelial cell-derived extracellular vesicles drive inflammasome activation and NTHi infection in COPD - Bateman, Georgia; Guo-Parke, Hong; Harvey, Caitlyn; Rodgers, Aoife; Krasnodembskaya, Anna; Linden, Dermot; Tirouvanziam, Rabindra; Borthwick, Lee A.; Fisher, Andrew J.; Coppinger, Judith; Kidney, Joe; Taggart, Clifford C. (Frontiers in Immunology, 2026)
Extracellular vesicles (EVs) are lipid-membrane bound vesicles that can be beneficial or detrimental depending on the content they carry. As epithelial cells are the first line of defense against harmful particles, this work explored the role of bronchial epithelial cell-derived EVs (CepEVs) in the pathogenesis and progression of chronic obstructive pulmonary disease (COPD). RNA sequencing of macrophages stimulated with CepEVs revealed the upregulation of various inflammasome-related genes, alongside significant IL-1b and IL-18 release, which could be attenuated with caspase-1 or NLRP3 inhibition. The proteome of CepEVs was also assessed, which highlighted a significant reduction in antibacterial proteins compared to healthy EVs (HepEVs). When functionally assessed in NTHi infection of THP-1 cells, pre-incubation with HepEVs stimulated NTHi clearance and reduced pro-inflammatory cytokine release by macrophages, which was reduced in CepEV-stimulated cells. This study shows for the first time that CepEVs are able to both prime and activate the inflammasome in healthy macrophages, and highlights EV-induced inflammasome inhibition as a potential therapeutic target for the dysregulated inflammation seen in COPD. Alongside the inflammasome, we were also able to show that CepEVs are deficient for multiple antibacterial proteins, and that one or more of these proteins are essential in mounting an immune response against NTHi in macrophages. This finding contributes to a potential therapeutic pipeline through the supplementation of the depleted antibacterial proteins in CepEVs, allowing for efficient bacterial clearance and reduced consequential inflammatory burden. CepEV co-incubation resulted in a persistent state of inflammation and infection. Both sets of findings contribute to the overall knowledge of COPD pathogenesis, and highlight epithelial EVs as key players in the propagation of inflammation and susceptibility to infection.